New Indicator to Measure Tax Burden – Proposal - Giday, András; Tatay, Tibor (Public Finance Quarterly, 2020)
This paper investigates to what extent tax burden can be used to compare countries with different pension systems. It was concluded that in one respect tax burden ratios used by international institutions fail to completely represent the share of income left after taxation, as the contributions paid to occupational pension funds are not included in total tax burden calculations. In our approach, however, in case of pension contributions it is the obligation of the payment itself and not the recipient of payment that matters. To this end, a new ratio called the ‘share of disposable current revenues’ was introduced to indicate the current income employers and employees can dispose of after all mandatory payments have been settled. Mandatory payments in this sense include all payment obligations employers cannot evade to pay to an institution (state, pension fund, etc.)